Do Morphological Changes in the Anterior Mandibular Region Interfere with Standard Implant Placement? A Cone Beam Computed Tomographic Cross-Sectional Study. (21st December 2020) - Fouda, Shaimaa M.; Ellakany, Passant; Madi, Marwa; Zakaria, Osama; Al-Harbi, Fahad A.; El Tantawi, Maha
Abstract : Objective . To determine the morphological features in the anterior mandibular region, the presence of lingual foramen and canal dimensions in Saudi subjects that would interfere with standard implant placement. Methods . CBCT scans of patients seeking implant treatment were examined. Based on the dentition status, patients were categorized into edentulous (group I) and dentulous (group I). On the panoramic view, the distance between the two mental foramina was divided into vertical segments of 10 mm width. In each segment, vertical bone height and buccolingual thickness at three levels (alveolar crest, 5 mm, and 10 mm apical to the crest) were assessed. The lingual foramen prevalence and canal features were assessed as well. Comparisons between the two groups regarding the assessed parameters were performed using the t -test. The percentage of edentulous mandibles with thickness <6 mm corresponding to the standard implant diameter was also calculated. Results . Following the inclusion and exclusion criteria, group I consisted of 45 subjects and group II comprised 26 subjects. Bone height and thickness at the crestal level were significantly less in edentulous (I) than dentate mandibles (II) (P < 0.0001 ). The lingual foramen was detected in 90% of patients. In both groups, males had significantly greater mandibular height than females (P = 0.02 and 0.005). At the crestal level, the thickness was <6 mm in 50% of the anterior mandibular segments. Conclusion . Half of the edentulous patients may receive normal size implants in the anterior interforaminal segments, while the other half will be limited to narrow implants (3.5 mm and less). The lingual foramen location, canal size, and position may represent another limitation for implant placement in that segment.